Influence voltage asymmetry transition asynchronous electric shock loads in - Savchenko, V.; Sinyavsky, O.; Savchenko, V. (Енергетика і автоматика, 2015)
The research of electromagnetic and electromechanical transients in asynchronous electric asymmetry in voltages. The influence of voltage unbalance of the length of the transition process and the established rate.